Genomic insights into the metabolic potential of a novel lignin-degrading and polyhydroxyalkanoates producing bacterium Pseudomonas sp. Hu109A. (January 2023) - Nawaz, Muhammad Zohaib; Shang, Huarong; Sun, Jianzhong; Geng, Alei; Ali, Sameh S.; Zhu, Daochen
Abstract: Lignin is the most abundant heterogeneous aromatic polymer present on planet Earth and is recalcitrant to degradation due to its complex structure, therefore, imposing a challenge to biorefinery procedures. Identifying new microbial strains with the potential to valorize lignin into useful compounds is indispensable to achieving green sustainable consumption. In this study, a novel Pseudomonas strain designated as Hu109A was isolated from the termite gut and the genome was sequenced and analyzed further. The genome contains a circular chromosome with the size of 5, 131, 917 bp having a GC content of 62.6% and 4698 genes. Genome annotation reveals that the strain possesses lignin-oxidizing enzymes such as DyP-type peroxidases, laccase, dioxygenase, and aromatic degradation gene clusters. The genome also contains O-methyltransferases which function in accelerating the lignin degradation by methylating the free hydroxyl phenolic compounds which in high concentration can inhibit the lignin peroxidase. Furthermore, the genome exhibits two gene clusters encoding the enzymes related to polyhydroxyalkanoates (PHA) synthesis. Pseudomonas strains are generally assumed to produce medium chain length PHAs (mcl-PHAs) only, however, strain Hu109A contains both Class II PHA synthase genes involved in mcl-PHAs and Class III PHA synthase gene involved in short-chain length PHAs (scl-PHAs). Gas Chromatography-Mass Spectrometry (GC-MS) analysis showed that using 1 g/L lignin as the sole carbon source, the maximum production of PHA observed was 103.68 mg/L, which increased to 186 mg/L with an increase in lignin concentration to 3 g/L. However, PHA production while using glucose as the sole carbon source was significantly lower than the lignin source, and maximum production was 125.6 mg/L with 3 g/L glucose. The strain Hu109A can tolerate a broad range of solvents including methanol, isopropanol, dimethylformamide, and ethanol, revealing its potential for industrial applications. Graphical abstract: Image 1 Highlights: Novel Pseudomonas strain was isolated from termite gut and the genome was sequenced. Genome exhibits the metabolic pathway for bioconversion of lignin to PHA. The bioconversion potential of the strain was experimentally evaluated. Pseudomonas strain Hu109A can tolerate a broad range of solvents. Represents a good candidate for lignin valorization into PHA at a commercial scale.